Material de apoio didático para o ensino de eletroquímica: Uma elaboração baseada nas concepções de um grupo de futuros professores - Rocha, Tatiane Aparecida Silva (2018)
The oxidation reactions are very present in our lives, as in photosynthesis, the fruits’ ripening, baterys’ functioning, as on other phenomena. However, some researches show that students of elementary and high school, and college, well as the chemistry teachers of high school, present alternative conceptions related to the content of Electrochemistry. In this context, this labor’s goal is analyse a group composed by graduating and graduated that participated a extension course about electrochemistry content's. Participated in the research, 5 graduated on chemistry that already had coursed the subject of Physicochemical of Solutions and Electrochemistry. Was accomplished six meeting, accounting a total workload of 40 hours, divided in presential moments and additional activities. The data was gathered by means of áudios, questionnaires and elaborated activities during the meetings. The results was analysed ant grouped on six categorys, allowing then, discuss better the answers. For the fulfillment of the investigation, was obtained by some official documents, didactic book of college and highs school, and in articles. The participants of the group presented deficulties related to the recognition of the cathod and anod, and write the anodic and cathodic semi-reactions. Because to dificulties presented by the participants, it was decided by elaboration of a didactical support material from teathers or future teachers of Elementary, High and Higher School (educational product), seeking for offer new aproaches surrounding some topics related to the contents of oxidation reactions focusing in electrochemial processes, making possible a succint study about the subject.